Analysis of market areas of mega malls in Istanbul - Vedia Dokmeci; Cem Beygo (European Regional Science Association (ERSA), 1998)
After 1980?s, restructuring of Istanbul has occurred in many fields and the increased number of mega malls is one of the most interesting aspects of the transformation of business facilities. Increase in the number of products as a result of globalization, advantages of the multistore shopping supported by the recreational facilities and increase in the income of the people and car use results in the development of mega malls mostly in the periphery of the city. These shopping facilities have attractive environments and have many advantages with respect to street shopping. Downtown areas of Istanbul held their dominant positions by reasons of the pulling power built up during the mass transportation era. After the construction of the periphery highways, subcenters have started to develop and while some of the mega malls fill the gap in retail trade in these new centers, some others create new subcenters by themselves. This study investigates the market areas of the mega malls with respect to their location in different zones of Istanbul and by taking into consideration different variables such as distance, our ownership, socio-economic and demographic characteristics of customers. The results of the research are that several of the potential locations are not served by the existing malls. Further research is suggested by doing simulation studies in order to evaluate the alternative location for the new malls.
Keywords: 330